2014
DOI: 10.1016/j.ijpara.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A review of global diversity in avian haemosporidians (Plasmodium and Haemoproteus: Haemosporida): new insights from molecular data

Abstract: Biogeographic patterns of parasite diversity are useful for determining how host-parasite interactions can influence speciation. However, variation in methodologies and sampling effort can skew diversity estimates. Avian haemosporidians are vector-transmitted blood parasites represented by over 1300 unique genetic lineages spread across over 40 countries. We used a global database of lineage distributions for two avian haemosporidian genera, Plasmodium and Haemoproteus, to test for congruence of diversity amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
274
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(291 citation statements)
references
References 97 publications
(121 reference statements)
7
274
0
10
Order By: Relevance
“…To separate these two lineages we would probably need to include additional molecular markers or to increase the size of the cytochrome b fragment sequenced. Given the small sample size of the birds screened in the present study, the number of lineages found is a considerable value and is comparable with other studies in the Neotropics that have found a large number of lineages (Fallon et al 2005, Lacorte et al 2013, Clark et al 2014. The high species richness we report agrees with the hypothesis that haemosporidian diversity may be a function of avian and/or vector host diversity, both of which are high in tropical continental regions (reviewed in Clark et al 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To separate these two lineages we would probably need to include additional molecular markers or to increase the size of the cytochrome b fragment sequenced. Given the small sample size of the birds screened in the present study, the number of lineages found is a considerable value and is comparable with other studies in the Neotropics that have found a large number of lineages (Fallon et al 2005, Lacorte et al 2013, Clark et al 2014. The high species richness we report agrees with the hypothesis that haemosporidian diversity may be a function of avian and/or vector host diversity, both of which are high in tropical continental regions (reviewed in Clark et al 2014).…”
Section: Discussionsupporting
confidence: 89%
“…The recent methodological advances in the detection of avian haemosporidian infection have led to an increase in the number of published surveys across the world (reviewed in Clark et al 2014). Some biogeographical patterns of haemosporidian distribution have been inferred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian haemosporidian parasites are transmitted by biting midges, louse flies, black flies and mosquitoes (ValkiĆ«nas 2005). More than 250 species of avian haemosporidians have been described and named according to morphological characteristics of parasite blood stages, and over 2 000 unique genetic haplotypes have been identified and recorded by molecular studies (ValkiĆ«nas 2005, Clark et al 2014). Because these blood parasites are abundant and diverse, they constitute excellent model organisms for the study of wildlife parasitology and have been the focus of research efforts for over 100 years (ValkiĆ«nas 2005, Bensch et al 2013.…”
mentioning
confidence: 99%
“…In other avian species, anemia and anorexia have been reported occasionally (8,14). Importantly, new records of Haemoproteus are discovered constantly and should still be monitored for effects on host condition (15).…”
Section: Introductionmentioning
confidence: 99%